(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The main thesis of the report: al-Farabi was the first major modernizer/reformer of Muslim thought, and today his religious and philosophical ideas are extremely relevant for the upcoming modernization of Muslim theology. Theological discourse, capable of responding to the challenges of our time, is impossible without a solid intellectual base, without philosophical culture. Only a philosophically oriented approach can lead to an adequate understanding of the problems faced by religion: here I mainly mean the monotheistic tradition – Judaism, Christianity and Islam. Key words: philosophy of al-Farabi, theological discourse, religion, history, Falsafa.